Teacher Strategies in Improving Students' Numeracy Literacy in Elementary Schools - Imam Jafar Shodiq (Agrapana Media, 2025)
The low level of students’ numeracy literacy in Indonesian primary education remains a crucial issue affecting the quality of learning outcomes and problem-solving abilities. This study aims to explore and analyze teachers’ strategies in enhancing numeracy literacy among students at Madrasah Ibtidaiyah Nurul Huda Ngasem, Bojonegoro. Using a qualitative descriptive approach, the research involved three teachers, one principal, and six students as participants, selected through purposive sampling. Data were collected through observations, interviews, and documentation, then analyzed using Miles and Huberman’s interactive model, consisting of data reduction, data display, and conclusion drawing. The findings reveal that teachers implement various strategies such as contextual learning, integration of numeracy into daily life, use of visual and digital media, and cross-disciplinary approaches. These strategies effectively improve students’ engagement, motivation, and understanding of numerical concepts. However, challenges remain in terms of varying student readiness, limited resources, and low parental involvement. To overcome these obstacles, teachers continuously engage in professional collaboration and involve parents through community-based numeracy programs. The study concludes that the success of numeracy literacy enhancement depends on consistent teacher innovation, institutional support, and active collaboration among educational stakeholders. Strengthening these aspects can significantly contribute to the development of analytical, logical, and problem-solving competencies among students in the context of 21st-century education.